5(3-x)+2(x+1)=-×+15
Soluções para a tarefa
Respondido por
0
Resposta: 1
Explicação passo-a-passo:
5(3-x)+2(x+1)=-x+15
15-5x+2x+2=-x+15
-5x+2x+x=15-15-2
-2x=-2 (-1)
2x=2
x=2/2
x=1
Respondido por
0
Explicação passo-a-passo:
Equação do primeiro grau:
5(3 - x) + 2(x + 1) = -x + 15
15 - 5x + 2x + 2 = - x + 15
-3x + 2 = - x
-2x = -2
x = 1
Espero ter ajudado bastante!)
Perguntas interessantes
Português,
10 meses atrás
Química,
10 meses atrás
Ed. Física,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás